Brucea javanica Leaf Extract Induced Apoptosis in Human Oral Squamous Cell Carcinoma (HSC2) Cells by Attenuation of Mitochondrial Membrane Permeability - Britanto Dani Wicaksono; Enos Tangkearung; Ferry Sandra (The Indonesian Biomedical Journal, 2015)
BACKGROUND: Brucea javanica extract has been reported to have anti-proliferative and cell death induction activities. B. javanica extract was reported to induce apoptosis through caspase cascade. Most of investigated B. javanica extracts were derived from seeds and fruits, or commercially available oil emulsion. Therefore we conducted a study on B. javanica leaf extract (BJLE) in oral cancer cells.METHODS: B. javanica leaves were collected, identified, minced, dried, extracted with distilled ethanol at room temperature for 24 hours, filtered and evaporated. Resulted BJLE was stored at 4°C. Human oral squamous cell carcinoma (HSC)-2 cells were fasted for 12 hours and treated with BJLE in various concentrations for 24 hours. Cells were then quantified with 3-(4,5-dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium bromide (MTT) assay, demonstrated with 4',6'-diamidino-2-phenylindole (DAPI) staining. To find out mitochondrial membrane permeability (MMP), mitochondrial membrane potential (ΔΨM) was analyzed.RESULTS: BJLE reduced percentage of viable HSC-2 cells in a concentration dependent manner. BJLE induced apoptosis in HSC-2 cells. With treatment of 50 μg/ml BJLE, fragmented nuclei were seen. ΔΨM of HSC-2 cells treated with 50 μg/ml BJLE were shifted to the left, meaning that BJLE induced reduction of ΔΨM and attenuation of MMP.CONCLUSION: Our results suggested that BJLE could induce apoptosis by attenuating MMP.KEYWORDS: Brucea javanica, leaf, apoptosis, HSC-2, MTT, DAPI, mitochondria, permeability